2020
DOI: 10.1038/s41388-020-1302-8
|View full text |Cite
|
Sign up to set email alerts
|

Entry and exit of chemotherapeutically-promoted cellular dormancy in glioblastoma cells is differentially affected by the chemokines CXCL12, CXCL16, and CX3CL1

Abstract: Glioblastoma multiforme (GBM) is a malignant brain tumor that evades therapy regimens. Since cellular dormancy is one strategy for surviving, and since chemokines determine the environmental conditions in which dormancy occurs, we investigated how chemokines affect temozolomide (TMZ)-promoted cellular dormancy entry and exit in GBM cells. TMZ administration over ten days promoted cellular dormancy entry, whereas discontinuing TMZ for a further 15 days resulted in resumption of proliferation. Co-administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Along with other chemokines, CXCL16 is involved in the regulation of the cellular dormancy of glioblastoma multiforme cells after exposure to temozolomide (TMZ) [ 191 ], a standard drug used in the treatment of this cancer [ 192 ]. Exposure of glioblastoma multiforme cells to TMZ stops cell division.…”
Section: Cxcl16→cxcr6 Axis and Anti-cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Along with other chemokines, CXCL16 is involved in the regulation of the cellular dormancy of glioblastoma multiforme cells after exposure to temozolomide (TMZ) [ 191 ], a standard drug used in the treatment of this cancer [ 192 ]. Exposure of glioblastoma multiforme cells to TMZ stops cell division.…”
Section: Cxcl16→cxcr6 Axis and Anti-cancer Therapymentioning
confidence: 99%
“…Exposure of glioblastoma multiforme cells to TMZ stops cell division. After discontinuation of the therapy, tumor cell proliferation resumes [ 191 ]. This process is regulated by the chemokine system, in particular CXCL16, and also by CX3C motif chemokine ligand 1 (CX3CL1) and CXC motif chemokine ligand 12 (CXCL12) [ 191 ].…”
Section: Cxcl16→cxcr6 Axis and Anti-cancer Therapymentioning
confidence: 99%
“…Another therapeutic strategy to maintain bone marrow microenvironment-induced dormancy of DTC may be to target the CXCL12/CXCR4 axis. In addition to what has been discussed above, it has also been suggested that delivery of CXCL12 to chemotherapy-induced dormant neuroblastoma cells led to down-regulation of genes associated with cell quiescence [ 294 ], and dormant breast tumor cells in lung metastatic sites had reduced CXCR4 expression [ 295 ], reinforcing the role CXCL12/CXCR4 signaling may play in reanimation of dormant tumor cells in metastatic sites.…”
Section: Rethinking Therapy For Bone Metastasesmentioning
confidence: 99%
“…In addition, the interaction between CXCR6 and CXCL16 leads to an increase in IL-4 secretion, which activates natural killer (NK) T cells to inhibit the proliferation of malignant cells ( 27 ). A study on gliomas revealed that CXCL16 and CX3CL1 downregulate the expression levels of vascular endothelial growth factor C ( 29 ), suggesting that they may inhibit tumor growth by decreasing angiogenesis. However, Takiguchi et al ( 30 ) found that soluble CXCL16 produced by mesenchymal stem cells (MSCs) via Wnt5a-Ror2 increased proliferation of human gastric cancer MKN45 cells expressing CXCR6.…”
Section: Hcc-associated Chemokinesmentioning
confidence: 99%
“…In the past, it was considered that CXCR4 was the only receptor of CXCL12. CXCL12/CXCR4 binds specifically and is commonly involved in various pathophysiological processes, such as anti-apoptotic and angiogenesis processes ( 29 ). Additionally, CXCL12/CXCR4 serves a key role in cell migration to multiple organs, including the liver, bone marrow and lungs ( 91 ).…”
Section: Hcc-associated Chemokinesmentioning
confidence: 99%